Long-term monitoring of Azorean forest spiders – Part 2 - Lhoumeau, Sébastien (2022)
The data we present hereafter are part of the long-term project SLAM (Long Term Ecological Study of the Impacts of Climate Change in the natural forest of Azores). This project started in 2012, and focuses on arthropod monitoring, with the aim to understand the impact of the drivers of biodiversity erosion on Azorean native forests (Azores, Macaronesia, Portugal). In this publication, we describe the second SLAM sampling database for the arachnofauna of native forests on two islands (Pico and Terceira), collected between 2019 and 2021.